Risk Factors Associated with Low Birth Weight - Rahfiludin, Mohammad Zen; Dharmawan, Yudhy (UI Scholars Hub, 2018)
Neonatal deaths are associated with preterm birth complications. The aim of this study was to analyze risk factors associated with LBW. This was a crosssectional study held in Bulu Primary Health Care, Temanggung, Central Java, Indonesia. The sample size required for this study was 69 based on the Slovin formula. Data were collected using questionnaires and semi-quantitative Food Frequency Questionnaire forms. Data on infant birth weight was taken from midwives’ delivery cohort records. Mid upper arm circumference (MUAC), hemoglobin level, blood pressure, maternal age, parity, nutritional intake, and serum transferrin receptor data were taken from the infant’s mother using a MUAC tape, automatic blood pressure monitor and blood laboratory analysis by Prodia. Data analysis procedures were carried out with quantitative methods. Descriptive statistics were analyzed as means and standard deviations. Inferential statistics used the chi-square test for bivariate analysis and binary logistic regression for multivariate analysis. The results of this study showed that mean infant birth weight was 2917.68 ± 374.673 kg. Inferential analysis showed that MUAC and pregnancy at a risky age were significant risk factors associated with LBW, while serum transferrin receptor levels, anemia, parity, energy and protein consumption levels, and systolic and diastolic blood pressure were nonsignificant risk factors. The probability of LBW in pregnant women with LILA under 23.5 cm and pregnancy at a risky age was 68.9%.